Peran Homeschooling dalam Mengembangkan Kecerdasan Spiritual Anak (Penelitian di Rumah Negla Desa Neglasari Kota Banjar) - Mariana, Nina; Koswara, S (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2018)
This study aims to explore the role of homeschooling in developing children's spiritual intelligence. This research uses descriptive analysis method. The research site is in Negla House, Desa Neglasari, Kota Banjar. Data collected through interviews, observations, and document review. Research respondents consisted of organizers of homeschooling education, parents of students, as well as other parties involved in organizing homeschooling, both directly and indirectly. This field research in education has found several conclusions. First, to optimize children's spiritual intelligence, homeschool organizers make systematic and measurable plans. In the planning, homeschool managers try to use children's psychology theories, developmental psychology, and learning models and strategies. Second, homeschooling education activities are carried out by developing a comfortable, pleasant learning environment, playing while learning, training, introducing the values of noble and religious characters